Immunological Prevalence of EBV in Rheumatoid Arthritis Iraqi Patients - Al-Nuaimy , Wafaa Ayad; Salloom, Dunya Fareed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
It has been hypothesized that infection with the Epstein-Barr virus (EBV) may play a role in the development of autoimmune illnesses, including rheumatoid arthritis (RA). This study aimed to investigate whether or not a history of infection with the virus is more common in RA patients compared to controls. Ninety samples ranging from 20 to 70 years old were obtained (45 patients plus 45 controls) between October 2022 and March 2023; each group included 37 females and 8 males. Rheumatoid arthritis (RA) patients who were chosen for this study were sent with a physician report for RA regular tests at Baghdad Teaching Hospital in Baghdad Province. The apparently healthy individuals were obtained (from family, friends, and other acquaintances after routine examinations) with age and sex matched with patients. We immunologically examined all 90 samples to detect Epstein-Barr virus (EBV) infection using both Epstein-Barr viral capsid Ag (VCA) IgG and Epstein Barr nuclear Ag (EBNA) IgG enzyme-linked immunosorbent assay (ELISA). The results showed that (66.7%) of RA patients and (60%) of controls were positive for VCA, while (57.8%) and (51.1%) were positive for EBNA in patients and controls, respectively. According to disease activity, there were (33.33%) and (34.62%) at high disease activity, while (66.67%) and (65.38%) at moderate disease activity were positive for VCA and EBNA, respectively. In conclusion, these findings do not reveal a relationship between EBV seroprevalence and RA, and as a result, they do not support the concept that a previous infection with EBV predisposes individuals to the development of RA